PENERAPAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN SISWA SEKOLAH DASAR TERHADAP KONSEP MATA PELAJARAN PENDIDIKAN PANCASILA - Chichi Malyuni; Musnar Indra Daulay; Putri Asilestari; Nasrul; Dwi Viora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' understanding of concepts in the Pancasila Education subject through the implementation of instructional videos. The research was conducted as a Classroom Action Research (CAR) at Grade V of SDN 013 Kumantan over two cycles, with each cycle consisting of two meetings. The research subjects were 12 students. Data collection techniques included observation, documentation, and learning outcome tests. The results showed that the use of instructional videos significantly enhanced students’ comprehension. In Cycle I, the percentage of students achieving mastery increased from 41.67% (pre-action) to 66.67%, and further increased to 100% in Cycle II. This improvement was also reflected in the students' average scores and active participation during the lessons. The conclusion of this research is that the use of instructional videos effectively and engagingly improves students’ understanding of Pancasila Education. Therefore, video-based learning media is highly recommended as an alternative tool to reinforce conceptual understanding and character education in primary schools.